Effect evaluation of fluid movement and rock properties for artificial seismic activity on hydrocarbons - Anoop Kanjirakat; Laith Abughaush; Arnel Carvero; Harris Rabbani; Mahmood Amani; Albertus Retnanto (Heliyon)
Despite the effectiveness of seismic stimulation in enhancing oil production from reservoirs, the impact of high-frequency vibrations on oil droplets confined within pore throats has not been adequately investigated. This laboratory-scale experimental study examines the impact of low and high-frequency sinusoidal vibrations in dislodging oil droplets trapped in a specific pore-throat region. Sinusoidal vibrations ranging from 10 to 80 Hz and with maximum displacement amplitudes of 1.2–0.06 mm are applied. By comparing the images captured prior to and after the application of seismic vibrations, the amount of oil recovered is determined. Commercial gasoline and diesel are used as trapped oil samples, and water is used as the injection fluid to bring out the effect of fluid viscosities in seismic dislodgment. While applying vibrations to trapped oil in the pore throat, three different recovery modes are observed: continuous, snap-off, and emulsified. The continuous oil recovery mode is observed in cases with minimal flow resistance through the pore throat, whereas a snap-off or intermittent recovery mode is observed when the flow resistance is high, and the vibration frequencies fall within the midrange of 40–60 Hz. An emulsified oil recovery mode is observed at high vibration frequencies. The amount of recovered oil increases as geometrical restrictions and trapped oil viscosity decrease. Seismic mobilization is observed to be directly proportional to the mobilization velocity and inversely proportional to the entrapped oil viscosity and geometrical restriction factors.